Teachers' Values and Social Competences: Towards a Social Skills Modelling Definition (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2018)
The demands that teaching is exerting on school practitioners have substantially changed in the last two decades. One of the most challenging aspects arises from an extremely fluid composition of the student population, with a larger variety of ethnicities, cultural traditions, and religions than in the past. The goals have shifted, as well, and they extend well beyond the transmission of specific subject contents. But can teachers effectively help the coming generations to develop social skills and common values, allowing them to promptly react to scenarios which are impossible to foresee? The aim of this review is to offer a coherent selection of previous findings related to the pivotal role of teachers at nurturing the moral acquisitions in their students. Four sections are dissecting evidence about teaching efficacy, teaching practice, value transmission and imitative learning. Through these elements, the possibilities of a successful intervention will be discussed and confronted with the unavoidable limitations and controversies.